Analisis Pengaruh Kebisisngan, Temperatur dan Pencahayaan Terhadap Produktivitas Kerja Pengeleman Amplop Secara Manual - Brury Jatmiko; Bambang Suhardi; Rahmaniyah Dwi Astuti (Performa: Media Ilmiah Teknik Industri, 2005)
This research explores the analysis of the optimum setting for the noise (80dB, 77dB, 80dB), temperature (18°C, 24°C, 34°C) and illumination (155lux, 200lux, 300lux) to optimize manually envelope folding jobs productivity. The analysis that will be implemented here is design experiments factorial method to determine the significant factors that influence manually envelope folding jobs productivity. Also, the response surface method will be applied to obtain the approximation model for manually envelope folding jobs productivity as a function of the factor found earlier so that the most optimum result can be obtained under a design optimization method.